Perspectives of bibliographic production inherent in process management in the public sector obtained through the ordinatio method - Queiroz, William da Silva; Rosa, Carla Regina Mazia; Feger, José Elmar (Brazilian Journal of Production Engineering, 2024)
Process management is fundamental to increasing the efficiency, productivity and quality of public services. Although its roots are historical, process management has expanded significantly in recent decades. Using the Ordinatio Method, a systematic search was conducted in the Scopus and Web of Science databases, focusing on articles published between 2014 and 2023. The initial search identified 286 articles, and after using exclusion criteria, and based on of relevance and quality, 20 articles were analyzed in depth. The main results indicate that the business process management (BPM) culture in public administration is influenced by factors such as professional experience, employee responsibilities and organization size. The analysis revealed additional challenges due to the complexity and bureaucracy of the government environment. However, digital transformation and the adoption of emerging technologies are modernizing administrative processes, improving the accessibility and personalization of public services. This study highlights the importance of structured practices and continuous innovations to overcome challenges and improve the quality of public services.
Keywords: Business Process Management; Federal University; Method Ordinatio